Polybrominated diphenyl ethers in indoor dust from Brazil: assessing demographic differences and human health exposure - de Souza Araujo, Juliana [UNESP]; dos Santos, Isadhora Camargo [UNESP]; Burgos Melo, Hansel David [UNESP]; Rosa, André Henrique [UNESP] (Springer Nature, 2024)
Indoor house dust is considered an important human exposure route to polybrominated diphenyl ethers (PBDEs), which has raised concern about their environmental persistence and toxicity properties. In this study, eight PBDEs (BDE-28, -47, -99, -100, -153, -154, -183, and -209) were determined in house dust from two cities with different socio-demographic characteristics from Brazil, examining possible relationships with factors that potentially influence contamination (population density, economic activities, presence of electronic equipment, and so on) and also estimating the risk of human exposure through oral ingestion and dermal contact. The Σ8PBDE concentration in Sorocaba city ranged between 380 and 4269 ng/g dw, while in Itapetininga city ranged from 106 to 1000 ng/g dw. In both regions, BDE-209 was the most abundantly found congener, followed by BDE-99. House dust from Sorocaba presented significantly greater concentrations of BDE-183 and BDE-209 than Itapetininga. Regarding risk exposure assessment, the estimated daily intake (EDI) of PBDEs was much lower than their respective reference doses (RfDs) in all pathways estimated (non-dietary ingestion and dermal contact). This study provided valuable data to improve the knowledge about the presence and exposure to PBDEs in Brazilian house dust in comparison to other developing countries and the need to control environmental pollution and protect human health.
Keywords: BDE-209; House dust; PBDEs; Risk assessment; Rural and urban areas